Variability of coastal upwelling south of Madagascar - Ramanantsoa, Heriniaina Juliano Dani (Department of Oceanography, 2019)
Madagascar’s southern coastal marine zone is a region of high biological productivity which supports a wide range of marine ecosystems, including fisheries. This high biological productivity is attributed to coastal upwelling. The thesis seeks to characterise the variability of the coastal upwelling south of Madagascar. The first part of the thesis provides new insights on the structure, variability and drivers of the coastal upwelling south of Madagascar. Satellite remote sensing is used to characterize the spatial extent and strength of the coastal upwelling. A front detection algorithm is applied to thirteen years of Multi-scale Ultra-high Resolution (MUR) Sea Surface Temperatures (SST) and an upwelling index is calculated. The influence of winds and ocean currents as drivers of the upwelling are investigated using satellite, in-situ observations, and a numerical model. Results reveal the presence of two well-defined upwelling cells. The first cell (Core 1) is located in the southeastern corner of Madagascar, and the second cell (Core 2) is west of the southern tip of Madagascar. These two cores are characterized by different seasonal variability, different intensities, different upwelled water mass origins, and distinct forcing mechanisms. Core 1 is associated with a dynamical upwelling forced by the detachment of the East Madagascar Current (EMC), which is reinforced by upwelling favourable winds. Core 2 which appears to be primarily forced by upwelling favourable winds, is also influenced by a poleward eastern boundary flow coming from the Mozambique Channel. This intrusion of Mozambique Channel warm waters could result in an asynchronicity in seasonality between upwelling surface signature and upwelling favourables winds. The second part of the thesis focuses on the interaction between the intrusion of warm water from Mozambique channel and the upwelling cell in Core 2. Cruise datasets, satellite remote sensing observations and model data analyses are combined to highlight the existence of a coastal surface poleward flow in the south-west of Madagascar: the South-west MAdagascar iv Coastal Current (SMACC). The SMACC is a relatively shallow (Coastal Current (SMACC). The SMACC is a relatively shallow (<300 m) and narrow (<100km wide) warm and salty coastal surface current, which flows along the south western coast of Madagascar toward the south, opposite to the dominant winds. The warm water surface signature of the SMACC extends from 22◦S (upstream) to 26.4◦S (downstream). The SMACC exhibits a seasonal variability: more intense in summer and reduced in winter. The average volume transport of its core is about 1.3 Sv with a mean summer maximum of 2.1 Sv. It is forced by a strong cyclonic wind stress curl associated with the bending of the trade winds along the southern tip of Madagascar. The SMACC directly influences the coastal upwelling regions south of Madagascar. Its existence is likely to influence local fisheries and larval transportpatterns, as well as the connectivity with the Agulhas Current, affecting the returning branch of the global overturning circulation. The last part of the thesis provides a holistic understanding of the inter-annual variability of the upwelling cells associated with the multiple forcing mechanisms defined in the first two parts of this work. Results reveal that the upwelling cells, Core 1 and Core 2, have different inter-annual variabilities. Inter-annual variability of Core 1 is associated with the East Madagascar Current (EMC) while Core 2 is linked with the South-west MAdagascar Coastal Current (SMACC). Inter-annual changes in the EMC occur as a result of oscillations in the South Equatorial Current (SEC) bifurcation off Madagascar, while the inter-annual variability in the SMACC is influenced by the cyclonic wind stress curl inter-annual variability. The upwelling is also linked with global/regional climate modes. Both Cores are highly correlated with the Subtropical Indian Ocean Dipole (SIOD). Core 2 is also correlated to the Indian Ocean Dipole (IOD). Both cores are significantly correlated with the El Ni˜no-Southern Oscillation (ENSO) after 12 months lag.